Women, the State, and Political Liberalization - Heba Raouf Ezzat (International Institute of Islamic Thought, 2001)
By late 1987 a wave of political changes appeared to be underway in the Middle East and North Africa. A number of Arab regimes, manifestly incapable of coping with growing problems of debt, unemployment, and corruption, took different measures towards more political participation. These countries witnessed political openings of various types, some more apparently significant than others but all promising changes that would lessen repression and open the way for greater political participation. In 1991 Laurie A. Brand started her project to study the effect of those changes on women in the region. She was also interested in studying the situation of women under the similar political and economic transformations that swept Eastern Europe in 1989-1990. While the latter continue to unfold, the openings that appeared in the Middle East and North Africa have in virtually all cases been closed. Despite that, the author pursued her project on women and political liberalization to explore the significance of culture - Islam as the omnipresent independent variable in Middle East politics - as opposed to structure. She also investigated the assumption that vibrant women's organizations can be important precursors to more democratic development, to determine what such organizations do and how they relate to the state, other political actors, and each other during such periods. Brand spotted some phenomena, such as the drop in the number of women legislators in local and national assemblies, changes in labor laws or their implementation at women's expense, and attempts to restrict women's personal or political rights - phenomena that have accompanied most of the "democratic'' transitions unfolding in the Middle East & North Africa region (MENA) ...